Impact of clinical pharmacist integration on diabetes management: a prospective cohort - Nur Burcu Kutluay; Muhammed Yunus Bektay; Betul Sumbul-Sekerci; Abdusselam Sekerci; Fikret Vehbi Izzettin (BMC Health Services Research)
Abstract Introduction Diabetes is a chronic disease with increasing prevalence. There is growing evidence pharmacist can contribute to clinical outcomes. This study aims to evaluate contribution of pharmacist to prediabetes and diabetes care. Methods A Prospective cohort study designed to evaluate the effects of pharmacist intervention on prediabetes (pDG) and type II diabetes mellitus (DMG) patients. The pharmacist conducted a detailed medication review and structured patient education during the first visit, followed by an evaluation of the interventions at the second visit (after 90 days). The effects were assessed by comparing fasting plasma glucose, HbA1c, the homeostasis model assessment-estimated insulin resistance (HOMA-IR), lipid profile, BMI, waist circumference, illness perception, and diabetes knowledge. Diabetes and preDiabetes knowledge was measured using the Diabetes and preDiabetes Knowledge Measurement Questionnaire (DKMQ and PKMQ), and illness perception with the Illness Perception Questionnaire-Revised (IPQ-R) The effect of pharmacist on diabetes care was assessed with a pre-post intervention comparison. The statistical significance was set at p < 0.05. Results A total of 145 (79 diabetes and 66 prediabetes) patients were included. The mean age of pDG and DMG were 45.79 ± 1.40 and 49.24 ± 1.08 years respectively. A statistically significant improvement was observed in weight, waist circumference, blood glucose, cholesterol, HbA1c, and HOMA-IR levels when comparing pre- and post-pharmacist intervention over the 90-day interval (p < 0.05). Statistically difference was observed in DKMQ, PKMQ and IPQ-R scores among the pDG and DMG (p < 0.001). Conclusion Pharmaceutical care services provided to diabetes patients had positive effects on disease prognosis, knowledge levels and disease perceptions. Patients with HbA1c level higher than 9% had the greatest benefit from pharmacist interventions.